PENERAPAN PENILAIAN BERACUAN PATOKAN DAN BERACUAN NORMA PADA SENI MUSIK DI SMP - Ermawati Ermawati; Jagar Lumban Toruan; Yos Sudarman (FBS Universitas Negeri Padang, 2012)
This study aimed to describe the approach of Reference Assessment Standard (PAP) and the Assessment Reference Norma (PAN) in the musical subjects in Class VII-C 4 SMP Negeri Padang. Research object-C Class VII students numbering 34 people, in which the current study, the researchers also conducted Field Teaching and assisting teachers in teaching the civil-semester school year 2011/2012. The research instrument used is the researchers themselves, research resource and archive Daily Exam grade students at UH) 1 and 2, Mid Semester Exam (UTS) and End Semester Examination (UAS). The results clarify that the use of PAP on the subjects of art music either to determine the quality of the individual student in mastering the art of learning music. However, to determine the final value is collected from all forms of the test, the teacher should use the PAN approach. With PAN, students who have different learning potential in music, nothing is likely to fail, and student learning outcomes in the form of the normal curve. Kata kunci: mendeskripsikan, norma, arsip, kualitas, kurva